Understanding the Influence of Vegetation on Urban Open-Channel Flow: A Numerical Modeling Approach in Monterrey, Mexico - N. L. Ramírez-Serrato; J. J. Nieto-Butrón; S. Barco-Coyote; F. D. Yépez-Rincon; M. P. Jácome Paz (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Flooding poses a persistent threat to urban areas, prompting the use of mathematical modeling to understand flow dynamics and delineate flood zones. Integrating vegetation into hydraulic models is crucial for assessing its effects on flow characteristics, sediment transport, and channel morphology. The Santa Catarina River in Monterrey, Mexico, experiences irregular water levels, leading to unchecked vegetation growth during dry seasons and vegetation loss during extreme weather events like hurricanes. This study utilized two hydraulic models, employing Digital Elevation and Surface Models alongside land use classifications and hydrological data from Hurricane Alex in 2010, to evaluate vegetation's impact on flood simulations. The results reveal significant changes in flood patterns due to vegetation, shifting the flood zone towards residential-commercial areas. Maximum depths increase from 10.70 to 16.78 meters, and affected areas deepen from 2 to 4.37 meters with the vegetation-inclusive model. These findings underscore vegetation's pivotal role in shaping urban flood pathways and advocate for integrating natural and human elements in flood risk management strategies. Future research avenues could explore socio-economic implications and evaluate cost-effective mitigation measures for diverse flooding scenarios.